A PU film based on carbon nanotube conductive multifunctional coating and a preparation method thereof
Patent Information
- Application Number
- CN202611215895.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
目前行业内采用喷涂SWCNTs分散液改性PU膜制备导电薄膜的技术路线已得到广泛研究,但现有技术仍存在诸多缺陷与不足:其一,SWCNTs比表面能高、范德华力作用强,极易团聚,导致分散液稳定性差,喷涂后导电涂层网络不连续,导电均匀性不佳,大面积制备时涂层均匀性与批次重复性较差,极大限制了该类导电PU薄膜的产业化推广与高端场景应用
本发明采用“PU基底预处理—SWCNTs分散液配置—均匀喷涂成膜—中低温加热固化—热压致密处理”实现单壁碳纳米管均匀铺展在PU膜表面,其中单壁碳纳米管承载核心导电功能,喷涂成膜后,可在PU膜表面搭接形成连续、贯通的三维导电网络,赋予薄膜稳定的导电性能,极低的添加量即可达到导电逾渗阈值,有效避免高填料掺杂导致的薄膜透光率下降、涂层变脆、柔韧性变差等问题,同时其优异的力学性能可跟随PU基底弯折、拉伸,保证导电网络不易断裂,提升导电薄膜的循环稳定性;分散剂采用羧甲基纤维素钠,可通过吸附包覆、静电排斥、空间位阻协同机制实现SWCNTs的均匀、稳定单分散,保障成膜后导电网络均匀性;去离子水作为分散体系的基础载体,无杂质、无离子干扰,作为绿色溶剂,搭配合适的分散剂,可均匀分散SWCNTs颗粒,构建均一、稳定的悬浮分散体系,同时体系粘度温和,适配喷涂工艺,无毒环保、成本低廉,适合规模化制备;而单纯的水分散体系表面张力大,直接喷涂易出现铺展不均、缩孔、干燥速度慢、涂层流挂等缺陷。无水乙醇可有效降低分散液整体表面张力,提升分散液在PU膜表面的润湿铺展性能,使喷涂涂层均匀平整;同时乙醇挥发速度快,可大幅缩短涂层干燥时间,提升涂层均匀性与平整度。此外,乙醇可调节分散液粘度,适配喷枪喷涂参数,提升大面积制备的工艺稳定性;进一步,添加噻吩基硅烷溶液改善分散体系中仅依靠羧甲基纤维素钠带来的绝缘性影响;噻吩基硅烷通过噻吩环与碳纳米管表面的π-π堆积实现非共价锚定分散,噻吩基硅烷的用量低于CMC,减少CMC的绝缘包裹,进一步提升涂层的导电性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to a PU film based on a carbon nanotube conductive multifunctional coating and its preparation method. Background Technology
[0002] Polyurethane (PU) films possess excellent flexibility, elasticity, bending resistance, and optical transmittance, along with low processing costs and strong interfacial adaptability, making them ideal flexible conductive substrates. Through design, they can achieve high tensile strength and high conductivity, making them suitable for flexible wearables, aerospace, and other fields. Single-walled carbon nanotubes (SWCNTs) are high-quality nanofillers for preparing high-performance flexible conductive coatings. Spray coating processes offer advantages such as ease of operation, low cost, large-area preparation, and controllable film thickness, making them suitable for the large-scale processing of flexible films. Currently, the technical route of preparing conductive films by modifying PU films with sprayed SWCNT dispersions has been widely studied in the industry. However, existing technologies still have many defects and shortcomings: Firstly, SWCNTs have high specific surface energy and strong van der Waals forces, making them prone to aggregation, resulting in poor dispersion stability. This leads to discontinuous conductive coating networks after spraying, poor conductivity uniformity, and poor coating uniformity and batch repeatability during large-area preparation, greatly limiting the industrialization and high-end application of this type of conductive PU film.
[0003] In conclusion, improving the stability of SWCNT dispersions for PU film surface coating is of great significance in order to solve the above problems. Summary of the Invention
[0004] The purpose of this invention is to provide a PU film based on a carbon nanotube conductive multifunctional coating and its preparation method, so as to solve the problems mentioned in the background art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing a PU film based on a carbon nanotube conductive multifunctional coating includes the following steps: taking a PU film, cleaning it, laying it flat and fixing it, spraying a SWCNTs dispersion and heating it to cure it, and finally performing a hot pressing densification treatment to form a carbon nanotube multifunctional coating on the surface of the PU film. The SWCNTs dispersion comprises single-walled carbon nanotubes and a dispersant; the dispersant comprises sodium carboxymethyl cellulose. Preferably, the preparation method of SWCNTs dispersion is as follows: single-walled carbon nanotubes are placed in deionized water, subjected to water bath sonication and low-speed stirring, then a dispersant is added for pre-dispersion, after pre-dispersion, intermittent sonication is performed, and finally anhydrous ethanol is added, stirred and mixed evenly for later use to obtain SWCNTs dispersion. The concentration of single-walled carbon nanotubes in the SWCNTs dispersion was 0.1 mg / mL; the mass ratio of the single-walled carbon nanotubes to the dispersant was 1:(1-10). The aspect ratio of the single-walled carbon nanotubes is 13000-15000; The process parameters for water bath ultrasound are: water bath temperature of 30-40℃, ultrasonic power of 400-600W, and low-speed stirring speed of 300-500rpm. The pre-dispersion time is 0.5-1 hour; The process parameters for intermittent ultrasound are: ultrasonic power of 200-500W, ultrasonic temperature of 25-40℃, and ultrasonic time of 1-2h. Sodium carboxymethyl cellulose is an anionic water-soluble polymer that coats the walls of SWCNTs through π-π adsorption. It inhibits the entanglement and aggregation of carbon nanotubes through electrostatic repulsion and steric hindrance. Ethanol reduces the surface tension of the pure water system and improves the wetting and spreading ability on the PU film surface. The solvent compound takes into account both dispersion stability and spray film formation. The instantaneous impact force generated by the ultrasonic cavitation effect peels off the tightly wrapped SWCNT bundles. Combined with the dispersant, it achieves uniform dispersion of single tubes / small bundles, improves the storage stability of the dispersion, and avoids stratification and sedimentation during the spraying process. Preferably, the spraying process parameters are: cross-spraying, spraying distance of 15-25cm, spraying speed of 10-20cm / s, number of spraying layers of 4-10, and inter-layer operation interval of 1-3min; The process parameters for heat curing are: temperature 60-100℃, time 30-60min; The process parameters for hot pressing densification are: hot pressing pressure of 5-10 MPa, temperature of 100-150℃, and time of 5-10 min. As the solvent evaporates completely, the high aspect ratio SWCNTs cross-link and interconnect with each other, forming a continuous three-dimensional conductive network on the surface of the PU film. This gives the insulating PU film stable conductive and antistatic properties, ultimately resulting in a flexible conductive PU composite film. More preferably, the preparation method of SWCNTs dispersion is as follows: thiophene silane is placed in formic acid solution and heated to 40-45℃ for 20-24h under nitrogen atmosphere to obtain thiophene silane solution; single-walled carbon nanotubes are placed in deionized water, thiophene silane solution is added and subjected to water bath sonication and low-speed stirring, then sodium carboxymethyl cellulose is added for pre-dispersion, followed by intermittent sonication, and finally anhydrous ethanol is added and stirred until homogeneous to obtain SWCNTs dispersion; Preferably, the preparation steps of thienylsilane are as follows: anhydrous ethylenediamine is placed in anhydrous methanol, and then a thienyl aldehyde compound is added and mixed. Under a nitrogen atmosphere, the mixture is heated to 60-65°C for 6-8 hours and then rotary evaporated. The mixture is then dissolved by ultrasonication in anhydrous methanol, and 3-glycidyl etheroxypropyltrimethoxysilane is added and mixed. The mixture is then heated to 60-65°C for 24 hours and then rotary evaporated to obtain thienylsilane. Preferably, the thiophene aldehyde compound is any one of thiophene-2-carboxaldehyde, thiophene[3,2-B]thiophene-2-carboxaldehyde, and 2,2'-bithiophene-5-carboxaldehyde; Preferably, the mass ratio of anhydrous ethylenediamine, thiophene aldehydes, and 3-glycidyl etheroxypropyltrimethoxysilane is (0.38-0.64):(0.23-0.42):1; More preferably, the mass ratio of single-walled carbon nanotubes, sodium carboxymethyl cellulose, and thiophene silane solution is 1:(1-5):(1.6-12.2): the thiophene silane solution is composed of thiophene silane and formic acid solution with a concentration of 0.01-0.05 mol / L in a volume ratio of 1 g:(40-100) mL; A PU film based on a conductive multifunctional coating of carbon nanotubes is prepared by the above-described preparation method.
[0006] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention employs a process of "PU substrate pretreatment—SWCNTs dispersion preparation—uniform spraying for film formation—medium-low temperature heating and curing—hot pressing densification treatment" to achieve uniform spreading of single-walled carbon nanotubes on the PU film surface. The single-walled carbon nanotubes carry the core conductive function. After spraying, they can overlap on the PU film surface to form a continuous, interconnected three-dimensional conductive network, endowing the film with stable conductivity. Extremely low addition amounts can reach the conductivity percolation threshold, effectively avoiding problems such as decreased film transmittance, coating brittleness, and reduced flexibility caused by high filler doping. Simultaneously, their excellent mechanical properties allow them to follow the bending and stretching of the PU substrate, ensuring the conductive network is not easily broken and improving the conductivity of the conductive film. Cyclic stability is crucial. Sodium carboxymethyl cellulose (SMC) is used as the dispersant, achieving uniform and stable monodispersion of SWCNTs through adsorption coating, electrostatic repulsion, and steric hindrance synergistic mechanisms, ensuring the uniformity of the conductive network after film formation. Deionized water serves as the basic carrier of the dispersion system, free from impurities and ion interference. As a green solvent, when combined with a suitable dispersant, it can uniformly disperse SWCNT particles, constructing a uniform and stable suspension dispersion system. Simultaneously, the system has a mild viscosity, is suitable for spraying processes, is non-toxic, environmentally friendly, and low-cost, making it suitable for large-scale preparation. In contrast, a simple water dispersion system has high surface tension, and direct spraying can easily lead to defects such as uneven spreading, pinholes, slow drying speed, and coating sagging. Anhydrous ethanol effectively reduces the overall surface tension of the dispersion, improving the wetting and spreading performance of the dispersion on the PU film surface, resulting in a uniform and smooth sprayed coating. Furthermore, the rapid evaporation rate of ethanol significantly shortens the coating drying time, improving coating uniformity and smoothness. In addition, ethanol can adjust the viscosity of the dispersion, adapt to the spray gun parameters, and improve the process stability of large-area preparation. Furthermore, the addition of thiophene silane solution improves the insulation effect caused by relying solely on sodium carboxymethyl cellulose in the dispersion system. Thiophene silane achieves non-covalent anchoring dispersion through the π-π stacking of thiophene rings and carbon nanotube surfaces. The amount of thiophene silane used is lower than that of CMC, reducing the insulating encapsulation of CMC and further improving the conductivity of the coating. Detailed Implementation
[0007] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0008] It should be noted that the following quantities are by weight, and there are no special restrictions on the suppliers of all raw materials involved in this invention. Exemplary examples include: The aspect ratio of single-walled carbon nanotubes is 13000; In the following examples, parts refer to parts by weight, and all raw materials mentioned above and others not mentioned are commercially available.
[0009] Example 1: This example provides a method for preparing a PU film based on a carbon nanotube conductive multifunctional coating, specifically including the following steps: Step 1: Place single-walled carbon nanotubes in deionized water to obtain a single-walled carbon nanotube concentration of 0.1 mg / mL. Perform water bath sonication and low-speed stirring. Pre-disperse for 1 h at a water bath temperature of 40℃, ultrasonic power of 400 W, and a rotation speed of 500 rpm. Then add sodium carboxymethyl cellulose at a mass ratio of 1:5 for single-walled carbon nanotubes and sodium carboxymethyl cellulose. After premixing evenly, place the mixture in an ultrasonic cell disruptor and start intermittent sonication at a power of 400 W, an ultrasonic temperature of 40℃, and a sonication time of 1.5 h to obtain a SWCNTs dispersion. Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the operating table, spray 20mL SWCNTs dispersion and 30mL SWCNTs dispersion respectively, heat to cure, cure at 80℃ for 50min, and finally perform hot pressing densification treatment, hot pressing at 120℃ and 10MPa for 8min to form a carbon nanotube multifunctional coating on the surface of the PU film.
[0010] Example 2: This example provides a method for preparing a PU film based on a carbon nanotube conductive multifunctional coating, specifically including the following steps: Step 1: Place single-walled carbon nanotubes in deionized water to obtain a single-walled carbon nanotube concentration of 0.1 mg / mL. Perform water bath sonication and low-speed stirring. Pre-disperse for 1 h at a water bath temperature of 40℃, ultrasonic power of 400 W, and a rotation speed of 500 rpm. Then add sodium carboxymethyl cellulose at a mass ratio of 1:3 for single-walled carbon nanotubes and sodium carboxymethyl cellulose. After premixing evenly, place the mixture in an ultrasonic cell disruptor and turn on intermittent sonication at a power of 400 W, an ultrasonic temperature of 40℃, and a sonication time of 1.5 h to obtain a SWCNT dispersion. Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the operating table, spray 20mL and 30mL of SWCNTs dispersion respectively, then heat to cure at 80℃ for 50min, and finally perform hot pressing densification treatment at 120℃ and 10MPa for 8min to form a carbon nanotube multifunctional coating on the surface of the PU film.
[0011] Example 3: This example provides a method for preparing a PU film based on a carbon nanotube conductive multifunctional coating, specifically including the following steps: Step 1: Place single-walled carbon nanotubes in deionized water to obtain a single-walled carbon nanotube concentration of 0.1 mg / mL. Perform water bath sonication and low-speed stirring. Pre-disperse for 1 h at a water bath temperature of 40℃, ultrasonic power of 400 W, and a rotation speed of 500 rpm. Then add sodium carboxymethyl cellulose at a mass ratio of 1:7 for single-walled carbon nanotubes. After premixing evenly, place the mixture in an ultrasonic cell disruptor and start intermittent sonication at a power of 400 W, an ultrasonic temperature of 40℃, and a sonication time of 1.5 h to obtain a SWCNT dispersion. Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the operating table, spray 20mL SWCNTs dispersion and 30mL SWCNTs dispersion respectively, heat to cure, cure at 80℃ for 50min, and finally perform hot pressing densification treatment, hot pressing at 120℃ and 10MPa for 8min to form a carbon nanotube multifunctional coating on the surface of the PU film.
[0012] Example 4: This example provides a method for preparing a PU film based on a carbon nanotube conductive multifunctional coating, specifically including the following steps: Step 1: Single-walled carbon nanotubes (SWCNTs) were placed in deionized water to obtain a SWCNT concentration of 0.1 mg / mL. They were then subjected to water bath sonication and low-speed stirring at a water bath temperature of 40°C, an ultrasonic power of 400 W, and a rotation speed of 500 rpm for 1 h. Then, sodium carboxymethyl cellulose (SCMC) was added at a mass ratio of 1:3 for SWCNTs. After premixing evenly, the mixture was placed in an ultrasonic cell disruptor and intermittent sonication was performed at a power of 400 W, a temperature of 40°C, and a duration of 1.5 h. Finally, an equal amount of anhydrous ethanol was added and stirring was continued to obtain the SWCNT dispersion. Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the operating table, spray 20mL and 30mL of SWCNTs dispersion respectively, then heat to cure at 80℃ for 50min, and finally perform hot pressing densification treatment at 120℃ and 10MPa for 8min to form a carbon nanotube multifunctional coating on the surface of the PU film.
[0013] Example 5: This example provides a method for preparing a PU film based on a carbon nanotube conductive multifunctional coating, specifically including the following steps: Step 1: Single-walled carbon nanotubes (SWCNTs) were placed in deionized water to obtain a SWCNT concentration of 0.1 mg / mL. They were then subjected to water bath sonication and low-speed stirring at a water bath temperature of 40°C, an ultrasonic power of 400 W, and a rotation speed of 500 rpm for 1 h. Then, sodium carboxymethyl cellulose (SCMC) was added at a mass ratio of 1:7 for SWCNTs. After premixing evenly, the mixture was placed in an ultrasonic cell disruptor and intermittent sonication was performed at a power of 400 W, a temperature of 40°C, and a duration of 1.5 h. Finally, an equal amount of anhydrous ethanol was added and stirring was continued to obtain the SWCNT dispersion. Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the operating table, spray 20mL SWCNTs dispersion and 30mL SWCNTs dispersion respectively, heat to cure, cure at 80℃ for 50min, and finally perform hot pressing densification treatment, hot pressing at 120℃ and 10MPa for 8min to form a carbon nanotube multifunctional coating on the surface of the PU film.
[0014] Example 6: This example provides a method for preparing a PU film based on a carbon nanotube conductive multifunctional coating, specifically including the following steps: Step 1: Place 1g of thienylsilane in 80mL of 0.02mol / L formic acid solution and heat to 40℃ for 22h under nitrogen atmosphere to obtain thienylsilane solution; place single-walled carbon nanotubes in deionized water to obtain a single-walled carbon nanotube concentration of 0.1mg / mL, add thienylsilane solution at a mass ratio of 1:4 of single-walled carbon nanotubes to thienylsilane solution, and perform water bath sonication and low-speed stirring. Pre-disperse for 1h at a water bath temperature of 40℃, ultrasonic power of 400W, and rotation speed of 500rpm. Then add sodium carboxymethyl cellulose at a mass ratio of 1:5 of single-walled carbon nanotubes to sodium carboxymethyl cellulose. After premixing evenly, place in an ultrasonic cell disruptor, turn on intermittent sonication at an ultrasonic power of 400W, ultrasonic temperature of 40℃, and ultrasonic time of 1.5h to obtain SWCNTs dispersion; Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the work table, spray SWCNTs dispersion and heat to cure, cure at 80℃ for 50 minutes, and finally perform hot pressing densification treatment, hot pressing at 120℃ and 10MPa for 8 minutes to form a carbon nanotube multifunctional coating on the surface of the PU film. The preparation steps of thiophene silane are as follows: 0.76 g of anhydrous ethylenediamine is placed in 20 mL of anhydrous methanol, and then 0.474 g of thiophene-2-carboxaldehyde is added and mixed. Under a nitrogen atmosphere, the mixture is heated to 60 °C for 8 h and then rotary evaporated. The mixture is then dissolved by ultrasonication in 20 mL of anhydrous methanol, and 2 g of 3-glycidyl etheroxypropyltrimethoxysilane is added and mixed. The mixture is then heated to 60 °C for 24 h and then rotary evaporated to obtain thiophene silane.
[0015] Example 7: This example provides a method for preparing a PU film based on a carbon nanotube conductive multifunctional coating, specifically including the following steps: Step 1: Place 1g of thienylsilane in 80mL of 0.02mol / L formic acid solution and heat to 40℃ for 22h under nitrogen atmosphere to obtain thienylsilane solution; place single-walled carbon nanotubes in deionized water to obtain a single-walled carbon nanotube concentration of 0.1mg / mL, add thienylsilane solution at a mass ratio of 1:4 of single-walled carbon nanotubes to thienylsilane solution, and perform water bath sonication and low-speed stirring. Pre-disperse for 1h at a water bath temperature of 40℃, ultrasonic power of 400W, and rotation speed of 500rpm. Then add sodium carboxymethyl cellulose at a mass ratio of 1:5 of single-walled carbon nanotubes to sodium carboxymethyl cellulose. After premixing evenly, place in an ultrasonic cell disruptor, turn on intermittent sonication at an ultrasonic power of 400W, ultrasonic temperature of 40℃, and ultrasonic time of 1.5h to obtain SWCNTs dispersion; Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the work table, spray SWCNTs dispersion and heat to cure, cure at 80℃ for 50 minutes, and finally perform hot pressing densification treatment, hot pressing at 120℃ and 10MPa for 8 minutes to form a carbon nanotube multifunctional coating on the surface of the PU film. The preparation steps of thienylsilane are as follows: 1.25g of anhydrous ethylenediamine is placed in 20mL of anhydrous methanol, and then 0.82g of 2,2'-bithiophene-5-carboxaldehyde is added and mixed. Under a nitrogen atmosphere, the mixture is heated to 60℃ for 8h and then rotary evaporated. The mixture is then dissolved by ultrasonication in 20mL of anhydrous methanol, and 2g of 3-glycidyl etheroxypropyltrimethoxysilane is added and mixed. The mixture is heated to 60℃ for 24h and then rotary evaporated to obtain thienylsilane.
[0016] Comparative example: Step 1: Single-walled carbon nanotubes (SWCNTs) were placed in anhydrous ethanol to obtain a SWCNT concentration of 0.1 mg / mL. They were then subjected to water bath sonication and low-speed stirring at a water bath temperature of 40°C, an ultrasonic power of 400 W, and a rotation speed of 500 rpm for 1 h. Ethyl cellulose was then added at a mass ratio of 1:5 between SWCNTs and sodium carboxymethyl cellulose. After premixing evenly, the mixture was placed in an ultrasonic cell disruptor and intermittent sonication was performed at a power of 400 W, a temperature of 40°C, and a duration of 1.5 h to obtain the SWCNT dispersion. Step 2: Take the PU film, wipe it with anhydrous ethanol to remove dust, grease and static electricity from the surface of the PU film, lay it flat and fix it on the operating table, spray 20mL SWCNTs dispersion and 30mL SWCNTs dispersion respectively, heat to cure, cure at 80℃ for 50min, and finally perform hot pressing densification treatment, hot pressing at 120℃ and 10MPa for 8min to form a carbon nanotube multifunctional coating on the surface of the PU film.
[0017] Performance testing: Conductivity test: The surface sheet resistance of the films with carbon nanotube multifunctional coatings prepared in Examples 1-7 and the comparative examples was measured by multi-point sampling using the four-probe method. The data are recorded in Table 1. Table 1
[0018] Conclusions: In Example 4, an equal amount of anhydrous ethanol was added as a process aid compared to Example 2. With a spraying volume of 30 mL, the resistance decreased, and the resistance data difference between the four points was small, reflecting the uniformity of the coating. In Examples 6 and 7, thiophene silane was added compared to Example 1, and the resistance decreased significantly, indicating that there is a synergistic effect between thiophene silane and sodium carboxymethyl cellulose. In the comparative example, when deionized water was replaced with anhydrous ethanol and the dispersant was replaced with ethyl cellulose, the resistance increased and the conductivity decreased significantly.
[0019] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a PU film based on a conductive multifunctional coating of carbon nanotubes, characterized in that, The process includes the following steps: after cleaning the PU film, it is laid flat and fixed, SWCNTs dispersion is sprayed and then heated to cure, and finally hot pressing is performed to form a carbon nanotube multifunctional coating on the surface of the PU film. The SWCNTs dispersion comprises single-walled carbon nanotubes and a dispersant; the dispersant comprises sodium carboxymethyl cellulose.
2. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 1, characterized in that, The preparation method of the SWCNTs dispersion is as follows: single-walled carbon nanotubes are placed in deionized water, subjected to water bath sonication and low-speed stirring, then a dispersant is added for pre-dispersion, followed by intermittent sonication, and finally anhydrous ethanol is added and stirred until homogeneous to obtain the SWCNTs dispersion.
3. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 1, characterized in that, The concentration of single-walled carbon nanotubes in the SWCNTs dispersion is 0.1-0.5 mg / mL; the mass ratio of single-walled carbon nanotubes to dispersant is 1:(1-10).
4. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 2, characterized in that, The aspect ratio of the single-walled carbon nanotubes is 13000-15000; the process parameters for water bath ultrasound are: water bath temperature 30-40℃, ultrasonic power 400-600W; low-speed stirring speed 300-500rpm; pre-dispersion time 0.5-1h; the process parameters for intermittent ultrasound are: ultrasonic power 200-500W, ultrasonic temperature 25-40℃, and ultrasonic time 1-2h.
5. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 1, characterized in that, The spraying process parameters are as follows: cross-spraying, spraying distance of 15-25cm, spraying speed of 10-20cm / s, number of spraying layers of 4-10, and interlayer operation interval of 1-3min.
6. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 1, characterized in that, The process parameters for heating and curing are: temperature 60-100℃ and time 30-60min; the process parameters for hot pressing densification are: hot pressing pressure 5-10MPa, temperature 100-150℃ and time 5-10min.
7. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 1, characterized in that, Alternatively: The preparation method of the SWCNTs dispersion is as follows: Thiophene silane is placed in formic acid solution and heated to 40-45℃ for 20-22h under nitrogen atmosphere to obtain thiophene silane solution; single-walled carbon nanotubes are placed in deionized water, thiophene silane solution is added and subjected to water bath sonication and low-speed stirring, then sodium carboxymethyl cellulose is added for pre-dispersion, after pre-dispersion is subjected to intermittent sonication, and finally anhydrous ethanol is added, stirred and mixed evenly for later use to obtain SWCNTs dispersion.
8. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 7, characterized in that, The preparation steps of the thiophene silane are as follows: anhydrous ethylenediamine is placed in anhydrous methanol, and then a thiophene aldehyde compound is added and mixed. Under a nitrogen atmosphere, the mixture is heated to 60-65℃ for 6-8 hours and then rotary evaporated. The mixture is then dissolved by ultrasonication in anhydrous methanol, and 3-glycidyl etheroxypropyltrimethoxysilane is added and mixed. The mixture is heated to 60-65℃ for 24 hours and then rotary evaporated to obtain the thiophene silane. The thiophene aldehyde compound is any one of thiophene-2-carboxaldehyde, thiophene[3,2-B]thiophene-2-carboxaldehyde, and 2,2'-bithiophene-5-carboxaldehyde. The mass ratio of anhydrous ethylenediamine, the thiophene aldehyde compound, and 3-glycidyl etheroxypropyltrimethoxysilane is (0.38-0.64):(0.23-0.42):
1.
9. The method for preparing a PU film based on a carbon nanotube conductive multifunctional coating according to claim 7, characterized in that, The mass ratio of the single-walled carbon nanotubes, sodium carboxymethyl cellulose, and thiophene silane solution is 1:(1-5):(1.6-12.2). The thiophene silane solution is composed of thiophene silane and a formic acid solution with a concentration of 0.01-0.05 mol / L at a volume ratio of 1 g:(40-100) mL.
10. A PU film based on a conductive multifunctional coating of carbon nanotubes, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.